2017
DOI: 10.3389/fneur.2017.00412
|View full text |Cite
|
Sign up to set email alerts
|

Stepping to the Beat: Feasibility and Potential Efficacy of a Home-Based Auditory-Cued Step Training Program in Chronic Stroke

Abstract: Background: Hemiparesis after stroke typically results in a reduced walking speed, an asymmetrical gait pattern and a reduced ability to make gait adjustments. The purpose of this pilot study was to investigate the feasibility and preliminary efficacy of home-based training involving auditory cueing of stepping in place.Methods: Twelve community-dwelling participants with chronic hemiparesis completed two 3-week blocks of home-based stepping to music overlaid with an auditory metronome. Tempo of the metronome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…However, due to the even higher cost, required experience, and time to use relative to instrumented mats, their application is also limited to research settings [12]. Therefore, a need exists for a valid tool that is capable of quantifying whole body asymmetry, while also being feasible for routine clinical adoption.Wearable accelerometers are a relatively low-cost alternative that are capable of measuring human movement from a variety of contexts while capturing parameters that are difficult to quantify from clinical inspection by the human eye [1,14]. Previous attempts to quantify measures of asymmetry indicative of spatiotemporal information of the feet with accelerometers have shown their feasibility, but also poor concurrent validity with reference standards of Gaitrite [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the even higher cost, required experience, and time to use relative to instrumented mats, their application is also limited to research settings [12]. Therefore, a need exists for a valid tool that is capable of quantifying whole body asymmetry, while also being feasible for routine clinical adoption.Wearable accelerometers are a relatively low-cost alternative that are capable of measuring human movement from a variety of contexts while capturing parameters that are difficult to quantify from clinical inspection by the human eye [1,14]. Previous attempts to quantify measures of asymmetry indicative of spatiotemporal information of the feet with accelerometers have shown their feasibility, but also poor concurrent validity with reference standards of Gaitrite [1].…”
mentioning
confidence: 99%
“…Wearable accelerometers are a relatively low-cost alternative that are capable of measuring human movement from a variety of contexts while capturing parameters that are difficult to quantify from clinical inspection by the human eye [1,14]. Previous attempts to quantify measures of asymmetry indicative of spatiotemporal information of the feet with accelerometers have shown their feasibility, but also poor concurrent validity with reference standards of Gaitrite [1].…”
mentioning
confidence: 99%
“…They have been used very effectively in the context of RAS-based motor rehabilitation programs for patients suffering from various movement disorders (21), mostly as a result of neurological diseases like stroke (22,23), Parkinson's disease (24,25) and multiple sclerosis (26). It has been consistently reported that stepping in time to a metronome can improve pathological gait in neurological patients e.g., in terms of increased walking speed (27), reduced step time asymmetry and step time variability (28) and increased stride length (29) as well as in healthy, but fallprone, older adults (24), even after only one training session (30).…”
Section: Rhythmic Auditory Stimulationmentioning
confidence: 99%
“…Much of the work to date on ARC has been ward or laboratory based, with many studies using treadmill walking [2,15], limiting application of findings to 'real world' ambulation. One recent study however has addressed the feasibility and potential efficacy of a homebased ARC training programme for stroke survivors and reported that this was feasible and well tolerated [16]. However, whilst finding improvements in walking and functional mobility, the training involved stepping in place/marching on the spot and these activities may not translate to community mobility.…”
Section: Introductionmentioning
confidence: 99%